In situ conversion to construct fast ion transport and high catalytic cathode for high-sulfur loading with lean electrolyte lithium–sulfur battery - Sun, Xun; Tian, Da; Song, Xueqin; Jiang, Bo; Zhao, Chenghao; Zhang, Yu; Yang, Li; Fan, Lishuang; Yin, Xiaoju; Zhang, Naiqing (Nano energy, 2022)
The difficulty of lithium ion transport and the slow redox reaction kinetics of polysulfide severely limit the performance of lithium-sulfur batteries under high sulfur loading and lean electrolyte conditions, thus hindering the practical process of lithium-sulfur batteries. Herein, FeF2 @rGO composites were used as sulfur host materials for lithium-sulfur batteries, which is in situ converted into LiF and FeS during the first discharging process, achieving rapid lithium ion transport and high catalytic activity simultaneously. The electrode delivered high discharge capacity and low capacity decay of 0.028% per cycle for 500 cycles. Even under elevated sulfur loading and lean electrolyte conditions, the electrode with FeF2 @rGO can exhibit high areal capacity of 12.3 mAh cm−2(12.7 mg cm−2 and 6 μL mg−1). [Display omitted] •The cathode with fast lithium ion transport was constructed by in-situ transformation method.•Reveal the evolution of host materials during operation and the formation of real catalysts.•The resulted cathodes exhibited high areal capacity of 12.3 mAh cm−2 under high sulfur loading and lean electrolyte conditions. (12.7 mg cm−2 and 6 μL mg−1).